The Role of Endothelial Related Circulating Biomarkers in COVID-19. A Systematic Review and Meta-analysis - Lampsas, Stamatios; Tsaplaris, Paraskevas; Pantelidis, Panteleimon; Oikonomou, Evangelos; Marinos, Georgios; Charalambous, Georgios; Souvaliotis, Nektarios; Mystakidi, Vasiliki-Chara; Goliopoulou, Athina; Katsianos, Efstratios; Siasos, Gerasimos; Vavuranakis, Michael-Andrew; et al. (Current Medicinal Chemistry, 2022)
Background: Several studies have revealed the link between Coronavirus Disease 2019 (COVID-19) and endothelial dysfunction. To better understand the global pattern of this relationship, we conducted a meta-analysis on endothelial biomarkers related to COVID-19 severity. Methods: We systematically searched the literature up to March 10, 2021, for studies investigating the association between COVID-19 severity and the following endothelial biomarkers: Intercellular Adhesion Molecule 1 (ICAM-1), Vascular Cell Adhesion Molecule 1 (VCAM-1), E-selectin, P-selectin, Von Willebrand Factor Antigen (VWFAg), soluble Thrombomodulin (sTM), Mid-regional pro-adrenomedullin (MR-proADM), and Angiopoietin-2 (Ang-2). Pooled estimates and mean differences (PMD) for each biomarker were reported. Results: A total of 27 studies (n=2213 patients) were included. Critically ill patients presented with higher levels of MR-proADM (PMD: 0.71 nmol/L, 95% CI: 0.22 to 1.20 nmol/L, p=0.02), E-selectin (PMD: 13,32 pg/ml, 95% CI: 4,89 to 21,75 pg/ml, p=0.008), VCAM-1 (PMD: 479 ng/ml, 95% CI: 64 to 896 ng/ml, p=0.03), VWF-Ag (PMD: 110.5 IU/dl, 95% CI: 44.8 to 176.1 IU/dl, p=0.04) and Ang-2 (PMD: 2388 pg/ml, 95% CI: 1121 to 3655 pg/ml, p=0.003), as compared to non-critically ill ones. ICAM-1, P-selectin and thrombomodulin did not differ between the two groups (p>0.05). Conclusion: Endothelial biomarkers display significant heterogeneity in COVID-19 patients, with higher MR-proADM, E-selectin, VCAM-1, VWF-Ag, and Ang-2 levels being associated with increased severity. These findings strengthen the evidence on the key role of endothelial dysfunction in disease progress.
Keywords: COVID-19